(untitled) (Вестник КазНУ. Серия историческая, 2018)
The student scientific group "Archaeologist" is part of the department of Archeology, ethnology and museology of the faculty of History, archeology and ethnology of the Al-Farabi Kazakh national university. Student scientific circle is a form of organization of scientific activity of students, which is expressed in attracting students to scientific work, facilitating the choice of a scientific direction, holding scientific sessions, listening to and discussing reports, participating in student scientific events of various levels.